PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH SEBAGAI DASAR PENYUSUNAN LAPORAN KEUANGAN USAHA MIKRO KECIL DAN MENENGAH (STUDI KASUS PADA UMKM UD. SANGGADOLU, KOTA SOE) - maak, ana yowester; Kerihi, Anthon S. Y.; Pau, Sarlin P. Nawa (Universitas Nusa Cendana, 2023)
The problem raised in this study is the recording of financial statements UD. Sanggadolu who is still doing the financial recording simply, not recorded in detail and not in accordance with current standards, in particular the Financial Accounting Standards of Micro and Medium Enterprises (SAK EMKM). The purpose of this research is to know the application of SAK EMKM as the basis of the preparation of the financial report of UMKM UD. Sanggadolu. The form of financial report based on SAKEMKM is the profit loss report, financial position report and records on financial reports. This research uses qualitative descriptive research methods, a kind of case study. The research informant is the owner of the UD. Sanggadolu, Bendahara and one of the staff of UD. Research is carried out through four stages, namely: data collection, data reduction, data presentation, and conclusion drawing. Based on the results of research related to the preparation of the financial report of UD. Sanggadolu based on EMKM SAK by adjusting the conditions of the existing transactions, the research results show that the elaboration of financial reports based on SAK EMKM is effective and accurate in achieving the objectives of business development, one of them through financial reports. With the financial statements that have been made, the owners can develop and expand their business more than the current conditions.